Pengaruh Diversifikasi Gender, Umur, Tenure Dan Pendidikan Terhadap profitabilitas Perusahaan Perbankan Di Bursa Efek Indonesia (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2018)
This study aims to prove and analyze the influence of demographic diversification or diversity of independent board members as measured by gender, age tenure and education of the company's ability to generate profits. The samples used are 22 banking companies that go public in Indonesia Stock Exchange. The analytical method used to validate the hypothesis is testing the panel data through the help of the Eviews program. Based on the results of tests that have been done found that the diversification of age and education does not affect the profitability of banking companies go public in the Indonesia Stock Exchange, while tenure and gender tenure and owned by independent board members have a significant effect on the profitability of banking companies that go public in Indonesia stock exchange